Enhancing Critical Thinking in Business Education through AI-Assisted Learning of Value-Based Pricing - Fahyuda Rammadan; Agus Wibowo (MANAJEMEN, 2025)
The development of Artificial Intelligence (AI) has brought a significant impact in various fields, including pricing strategies. Value-Based Pricing as an approach that focuses on the perception of customer value is now increasingly optimized through the integration of AI technology. The study aims to explore how AI can support value-based decision-making through complex data processing and predictive analytics, as well as how critical thinking skills remain a key competency in interpreting results and establishing sustainable pricing strategies. This approach emphasizes the importance of synergy between technological sophistication and human cognition, in order to produce decisions that are not only efficient but also ethical and value-oriented in the long term. The results of this study show that the application of AI in Value-Based Pricing can improve the accuracy and speed of analysis, but still requires an active role of critical thinking in the context of interpretation and strategic decision-making.